Prenatal yoga sebagi solusi mengatasi keluhan fisik dan melancarkan proses persalinan pada ibu hamil di PMB Jurusan Kebidanan Poltekkes Kemenkes Yogyakarta - Atik Ismiyati (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
One of the causes of maternal death is due to long parturition, long parturition is influenced by several factors such as maternal strength factors, the flexibility of the birth canal, and maternal psychology. Pregnancy will experience several physical and psychological complaints. The purpose of doing prenatal yoga can overcome these complaints while preparing for labor to run smoothly. This activity was carried out 3 times in PMB Poltekkes Yogyakarta Midwifery Department which was attended by 32 participants. The results of the evaluation of this activity participants felt complaints during pregnancy decreased such as aches, difficulty sleeping, and the body feels more relaxed.